OPTIMALISASI CLASSROOM MANAGEMENT DALAM MEMBENTUK KARAKTER DISIPLIN SISWA: UJI MEDIASI POSITIVE DISCIPLINE - Hasugian, Putri Gagan; Muslim, Fachruddiansyah; Ramalia , Aminah (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the effect of classroom management on positive discipline, the effect of positive discipline on students’ discipline character, and the mediating role of positive discipline in the relationship between classroom management and students’ discipline character at SMAN 12 Kota Jambi.Methods: This research employed a quantitative approach with an explanatory design. The population consisted of 907 students of SMAN 12 Kota Jambi, with a sample of 167 students selected through purposive sampling. Data were collected using questionnaires and analyzed using SmartPLS. The analysis techniques included validity and reliability testing, outer model evaluation, inner model evaluation, and hypothesis testing.Results: The results show that classroom management has a positive and significant effect on positive discipline. Furthermore, positive discipline has a positive and significant effect on students’ discipline character. In addition, positive discipline is proven to mediate the relationship between classroom management and students’ discipline character significantly. This indicates that effective classroom management will have a stronger impact on shaping students’ discipline character when supported by the implementation of positive discipline.Novelty: This study provides empirical evidence on the role of positive discipline as a mediating variable in strengthening the influence of classroom management on students’ discipline character, particularly at the senior high school level, which is still limited in previous research.